Anatomy of the oral cavity of hylid larvae from the genera Aplastodiscus, Bokermannohyla, and Hypsiboas (Amphibia, anura): Description and systematic implications - D'Heursel, Anne; Haddad, Cwo F. B. (Soc Study Amphibians Reptiles, 2007)
Internal larval oral anatomy was used to explore morphological diversity and its contribution to the systematics of the genera Aplastodiscus, Bokerinannohyla, and Hypsiboas, belonging to the tribe Cophomantini. Internal oral morphology was examined for tadpoles of 12 species. All species have a large pair of infralabial papillae on the buccal floor and other papillae on the prelingual region. In Aplastodiscus and Bokerinannohyla, the large infralabial papillae have digitiform secondary projections. The number and arrangement of the buccal floor papillae varies among species, but they are more numerous in Aplastodiscus and Bokerinannohyla. The arrangement of the postnarial papillae is variable, but in Aplastodiscus and Bokerinannohyla, they show a definite, inverted V-shape pattern. The lateral ridge papillae are more complex in larvae of Bokertnannohyla with long digitiform secondary projections. Tadpoles of only Aplastodiscus albofrenatus, Aplastodiscus eugenioi, and Bokerinannohyla luctuosa have papillae on the buccal roof arena and larvae of all species have lateral roof papillae except Hypsiboas albomarginatus and Hypsiboas cinerascens. Larvae of Aplastodiscus, Bokermannohyla, and Hypsiboas presumably share the presence of vacuities anterior to the internal nares; although this character state is clearly synapomorphic within hylids, it is still uncertain whether it is exclusive of these three genera or whether it is present in the other genera of the tribe Cophomantini (Hyloscirtus and Myersiohyla). The inclusion of internal oral anatomy characters, such as the narial vacuities, in systematic studies is certainly valuable because it will provide additional information toward the understanding of phylogenetic relationships.